Analisis Sentimen Pembangunan Infrastruktur di Indonesia dengan Automated Lexicon Word2Vec dan Naive-Bayes - Ananda Fitri Niasita; Putra Pandu Adikara; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Infrastructure development is a project that being intensively carried out by the current government. With the existence of good infrastructure, the government hopes that in the future the economy and the level of Indonesian welfare will increase. Infrastructure development attracts the community attention. Various comments regarding this project were mentioned through social media, for example Twitter. The number of pros and cons community comparisons known by using sentiment analysis. In this case, sentiment analysis uses a lexicon dictionary to determine whether the data is positive or negative. The lexicon dictionary created automatically using the Word2Vec method. Word2Vec method is used to find closeness between words.. Then, the sentiment class is determine using the Naive-Bayes method. This study uses 100 training data and 50 testing data divided into positive and negative sentiments. The highest accuracy value are 64% with precision of 0.36, re-call of 0.818 and f-measure of 0.5.